Advances in Lead-Free Perovskite Single Crystals: Fundamentals and Applications - Tailor, Naveen Kumar; Kar, Shaoni; Mishra, Pranjal; These, Albert; Kupfer, Christian; Hu, Hanlin; Awais, Muhammad; Saidaminov, Makhsud; Dar, M. Ibrahim; Brabec, Christoph; Satapathi, Soumitra (ACS Materials Letters, 2021)
With rapid progress in the deployment of metal halide perovskites in various device applications such as solar cells, light-emitting devices, field-effect transistors, photodetectors, etc., the next eminent focus is on the single crystals of these materials. With a lack of grain boundaries and low trap densities, remarkably long charge carrier diffusion lengths, and high ambient and operational stabilities, this class of materials seems greatly promising. Yet, the growing concern for lead toxicity in commercial semiconductor devices has entailed a thrust in the research of alternative lead-free perovskites, including their single crystalline forms. However, there is still no consolidated account of the state-of-the-art in this domain and accordingly, countless feasible systems still remain unexplored. To bridge this gap, we attempt to provide here, an up-to-date overview of lead-free perovskite single crystals with respect to their synthesis methods, structural diversity, stability, photophysical and electrical properties, and device applications. We discuss various approaches to designing, modeling, fabricating, and characterizing new single-crystal systems and conclude with some critical insights for further investigating this field of research.
CRIS-Team Scopus Importer:2021-07-16

Beginner's Guide to Visual Analysis of Perovskite and Organic Solar Cell Current Density–Voltage Characteristics - These, Albert; Koster, L. Jan Anton; Brabec, Christoph; Le Corre, Vincent Marc (Advanced Energy Materials, 2024)
The current density–voltage characteristic (J–V) is a critical tool for understanding the behavior of solar cells. This study presents an overview of the key aspects of J–V analysis and introduces a user-friendly flowchart that facilitates the swift identification of the most probable limiting process in a solar cell, based mainly on the outcomes of light-intensity-dependent J–V measurements. The flowchart is developed through extensive drift-diffusion simulations and a rigorous review of the literature, with a specific focus on perovskite and organic solar cells. Moreover, the flowchart proposes supplementary experiments that can be conducted to obtain a more precise prediction of the primary performance losses. It therefore serves as an optimal starting point to analyse performance losses of solar cells.
CRIS-Team Scopus Importer:2024-04-19
Keywords: current-voltage characteristic; drift-diffusion simulation; organic solar cell; perovskite solar cell; photovoltaics

Binary cations minimize energy loss in the wide-band-gap perovskite toward efficient all-perovskite tandem solar cells - Zhang, Kaicheng; Liu, Chao; Peng, Zijian; Li, Chaohui; Tian, Jingjing; Li, Canru; García Cerrillo, José; Dong, Lirong; Streller, Fabian; Späth, Andreas; Musiienko, Artem; Englhard, Jonas; et al. (Joule, 2024)
Perovskite-based tandem solar cells stand at the forefront of photovoltaic innovation due to their exceptional performance and cost-effective fabrication. This study focuses on minimizing energy losses within a 1.80 eV perovskite sub-cell. We demonstrate that the surface treatment of perovskite with binary guanidinium bromide and 4-fluorophenylammonium iodide synergistically reduces defect densities and adjusts interfacial energy-level alignment. The enhanced passivation effect and the formation of a surface dipole significantly reduce nonradiative recombination and transport losses, leading to a notable increase in the open-circuit voltage and fill factor product, thereby achieving an impressive power conversion efficiency (PCE) of 19.0%. The reproducibility of these findings is confirmed by consistent results across different laboratories. Furthermore, integration with a narrow-band-gap perovskite yields an all-perovskite tandem device with a PCE of 27.2%. This comprehensive understanding of the pivotal role of spacer cations in surface treatment significantly advances the pathway toward efficient perovskite photovoltaics.
CRIS-Team Scopus Importer:2024-08-30
Keywords: 2D phases; all-perovskite tandem solar cell; energy loss; energy-level alignment; nonradiative recombination; passivation; spacer cations; surface dipole; surface treatment; wide band-gap perovskite

Characterization of Aerosol Deposited Cesium Lead Tribromide Perovskite Films on Interdigited ITO Electrodes - These, Albert; Khansur, Neamul Hayet; Almora, Osbel; Luer, Larry; Matt, Gebhard; Eckstein, Udo; Barabash, Anastasia; Osvet, Andres; Webber, Kyle Grant; Brabec, Christoph (Advanced Electronic Materials, 2021)
Aerosol deposition (AD) is a promising additive manufacturing method to fabricate low-cost, scalable films at room temperature, but has not been considered for semiconductor processing, so far. The successful preparation of cesium lead tribromide (CsPbBr3) perovskite films on interdigitated indium tin oxide (ITO) electrodes by means of AD is reported here. The 20–35 µm thick layers are dense and have good adhesion to the substrate. The orthorhombic Pnma crystal structure of the precursor powder was retained during the deposition process with no signs of defect formation. The formation of electronic defects by photoluminescence spectroscopy is investigated and found slightly increased carrier recombination from defect sites for AD films compared to the powder. A nonuniform defect distribution across the layer, presumably induced by the impact of the semiconducting grains on the hard substrate surface, is revealed. The opto-electronic properties of AD processed semiconducting films is further tested by electrical measurements and confirmed good semiconducting properties and high responsivity for the films. These results demonstrate that AD processing of metal halide perovskites is possible for opto-electronic device manufacturing on 3D surfaces. It is believed that this work paves the way for the fabrication of previously unimaginable opto-electronic devices by additive manufacturing.
CRIS-Team Scopus Importer:2021-01-22
Keywords: aerosol deposition; hysteresis; impedance spectroscopy; inorganic perovskites; photoluminescence spectroscopy

Enhancing deep visible-light photoelectrocatalysis with a single solid-state synthesis: Carbon nitride/TiO2 heterointerface - Silva, Ingrid F.; Pulignani, Carolina; Odutola, Jokotadeola; Galushchinskiy, Alexey; Texeira, Ivo F.; Isaacs, Mark; Mesa, Camilo A.; Scoppola, Ernesto; These, Albert; Badamdorj, Bolortuya; Ángel Muñoz-Márquez, Miguel; Zizak, Ivo; et al. (Journal of Colloid and Interface Science, 2025)
Visible-light responsive, stable, and abundant absorbers are required for the rapid integration of green, clean, and renewable technologies in a circular economy. Photoactive solid–solid heterojunctions enable multiple charge pathways, inhibiting recombination through efficient charge transfer across the interface. This study spotlights the physico-chemical synergy between titanium dioxide (TiO2) anatase and carbon nitride (CN) to form a hybrid material. The CN(10%)-TiO2(90%) hybrid outperforms TiO2 and CN references and literature homologs in four photo and photoelectrocatalytic reactions. CN-TiO2 achieved a four-fold increase in benzylamine conversion, with photooxidation conversion rates of 51, 97, and 100 % at 625, 535, and 465 nm, respectively. The associated energy transfer mechanism was elucidated. In photoelectrochemistry, CN-TiO2 exhibited 23 % photoactivity of the full-spectrum measurement when using a 410 nm filter. Our findings demonstrate that CN-TiO2 displayed a band gap of 2.9 eV, evidencing TiO2 photosensitization attributed to enhanced charge transfer at the heterointerface boundaries via staggered heterojunction type II.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Benzylamine photooxidation; CN-TiO; Heterointerface; Hydrogen production; TiO

Overcoming Temperature-Induced Degradation of Silver Nanowire Electrodes by an Ag@SnOx Core-Shell Approach - Kalancha, Violetta; These, Albert; Vogl, Lilian; Levchuk, Ievgen; Zhou, Xin; Barr, Maissa; Bruns, Mark; Bachmann, Julien; Virtanen, Sannakaisa; Spiecker, Erdmann; Osvet, Andres; Brabec, Christoph; et al. (Advanced Electronic Materials, 2022)
Transparent electrodes consisting of silver nanowires (Ag NWs) are a solution-processed alternative to commonly used indium tin oxide electrodes. Here, Ag NW electrodes protected by a tin oxide (SnOx) are explored and unprecedented thermal stability is found. While unprotected Ag NW electrodes fail at 250 degrees C, the SnOx Ag NW electrodes remain stable for 40 h at 250 degrees C and withstand high temperatures up to 500 degrees C for short times. First, an optimized method of synthesis that provides uniform Ag NWs with high reproducibility is used. Afterward, a SnOx shell is formed in a wet chemical reaction. Fabrication of highly conductive electrodes requires thermal annealing at 300 degrees C for 5 min under ambient atmosphere. Electrodes with a sheet resistance as low as 20 ohm sq(-1) and visible transmittance of 84% are demonstrated. It is shown that a approximate to 2 nm thick SnOx shell effectively protects the Ag NWs in a temperature range between 200 and 500 degrees C, whereas unprotected Ag NWs suddenly fail at temperatures beyond 200 degrees C. It is strongly anticipated that these improvements in the stability of Ag NWs open a large field of further investigations and applications.
CRIS-Team WoS Importer:2022-02-11

Reducing Open-Circuit Voltage Losses in All-Inorganic Perovskite Cells by Dedoping - Peng, Zijian; Tian, Jingjing; Zhang, Kaicheng; These, Albert; Xie, Zhiqiang; Zhao, Yicheng; Osvet, Andres; Guo, Fei; Lüer, Larry; Li, Ning; Brabec, Christoph (ACS Energy Letters, 2023)
CsPbI2Br is an attractive photovoltaic material due to its promising optoelectronic properties. However, the corresponding perovskite solar cells (PSCs) with p-i-n configuration suffer from low open-circuit voltage (VOC) and fill factor (FF), limiting their application in tandem solar cells. Here, we propose using the fullerene ICBA as the electron charge transporting layer (ETL), forming a better interfacial contact and enhancing the internal quasi-Fermi level splitting (QFLS). A further reduction of VOC losses of around 0.1 V was achieved by an ultrathin phenethylammonium chloride (PEACl) layer between the perovskite and the ETL. We precisely study the VOC improvement and find that passivation of surface recombination contributes only 20 mV, while more importantly, a major increase of 80 mV is achieved by dedoping the perovskite surface, which removes a non-negligible electron extraction barrier. Our results give helpful direction regarding how to further improve VOC in p-i-n perovskite cells.
CRIS-Team Scopus Importer:2023-04-21

Self-Healing Cs3Bi2Br3I6 Perovskite Wafers for X-Ray Detection - Daum, Manuel; Deumel, Sarah; Sytnyk, Mykhailo; Afify, Hany A.; Hock, Rainer; Eigen, Andreas; Zhao, Baolin; Halik, Marcus; These, Albert; Matt, Gebhard; Brabec, Christoph; Tedde, Sandro F.; et al. (Advanced Functional Materials, 2021)
Self-healing of defects imposed by external stimuli such as high energy radiation is a possibility to sustain the operational lifetime of electronic devices such as radiation detectors. Cs3Bi2Br3I6 polycrystalline wafers are introduced here as novel X-ray detector material, which not only guarantees a high X-ray stopping power due to its composition with elements with high atomic numbers, but also outperforms other Bi-based semiconductors in respect to detector parameters such as detection limit, transient behavior, or dark current. The polycrystalline wafers represent a size scalable technology suitable for future integration in imager devices for medical applications. Most astonishingly, aging of these wafer-based devices results in an overall improvement of the detector performance—dark currents are reduced, photocurrents are increased, and one of the most problematic properties of X-ray detectors, the base line drift is reduced by orders of magnitude. These aging induced improvements indicate self-healing effects which are shown to result from recrystallization. Optimized synthetic conditions also improve the as prepared X-ray detectors; however, the aged device outperforms all others. Thus, self-healing acts in Cs3Bi2Br3I6 as an optimization tool, which is certainly not restricted to this single compound, it is expected to be beneficial also for many further polycrystalline ionic semiconductors.
CRIS-Team Scopus Importer:2021-08-27
Keywords: bismuth halides; lead-free perovskites; photoconductors; self-healing; X-ray detection

Shape-Controlled Solution-Epitaxial Perovskite Micro-Crystal Lasers Rivaling Vapor Deposited Ones - Afify, Hany A.; Rehm, Viktor; Barabash, Anastasia; These, Albert; Zhang, Jiyun; Osvet, Andres; Schüßlbauer, Christoph; Thiel, Dominik; Ullrich, Tobias; Dierner, Martin; Przybilla, Thomas; Will, Johannes; et al. (Advanced Functional Materials, 2022)
Epitaxial growth methods usually need dedicated equipment, high energy consumption to maintain pure vacuum conditions and evaporation of source materials, and elevated substrate temperatures. Solution epitaxial growth requires nothing of that but is rarely used because the achieved microstructures are of low quality, not homogeneous, and finally exhibit worse performances in devices. Here, an antisolvent-vapor-assisted-crystallization of metal-halide-perovskites as a method overcoming these disadvantages is demonstrated. The methylammonium lead tribromide exhibits van-der-Waals type of epitaxial growth on mica substrates, resulting in micro-crystallites whose shape can be controlled to be either triangular micro-prism or micro-cuboid. These micro-crystallites act as optical resonators supporting various optical modes and lasing is achieved under optical excitation with low thresholds and record high environmental stability. Selecting suitable resonators from a large variety of sizes allows control of mode spacing and finally mono-mode operation, considered to be an important feature of semiconductor laser devices. The achieved results are essentially competitive to those obtained by vapor phase epitaxial microstructures, highlighting that epitaxy of high-quality optoelectronic device structures is feasible by minimum technological efforts and energy consumption, which are of increasing importance considering issues such as global warming and the current energy crisis.
Created from Fastlane, WoS look-up

Solution-Growth Liquid-Phase Epitaxy of CsPbBr3 on NaCl by Optimizing the Substrate Dissolution - Elia, Jack; Levchuk, Ievgen; Hou, Yi; Matt, Gebhard; These, Albert; Zhao, Yicheng; Zhang, Jiyun; Forberich, Karen; Osvet, Andres; Götz, Klaus; Prihoda, Annemarie; Wu, Mingjian; et al. (Journal of Physical Chemistry C, 2023)
Since the earliest days of liquid-phase epitaxy (LPE) research, substrate stability has been a prerequisite for investigating nucleation and epitaxial growth. For flux- and melt-growth LPE, soluble substrates have always been viewed as problematic and difficult. However, solution-growth LPE transforms this disadvantage into a benefit by facilitating the creation of graded interfaces. In this study, we investigated the nucleation and growth of solution-grown LPE in the evaporation mode of soluble CsPbBr3 on freshly cleaved NaCl single-crystal substrates. Only two of the four main types of CsPbBr3 crystallization observed are epitaxial. The microscopic observation of composition gradients at the interface of CsPbBr3 grains and substrates reveals a promising opportunity to manipulate the lattice constant at the interface by simply controlling the temperature and concentration.
CRIS-Team Scopus Importer:2023-12-08

Squeezing the Threshold of Metal-Halide Perovskite Micro-Crystal Lasers Grown by Solution Epitaxy - Zhou, Shuyu; Rehm, Viktor; Afify, Hany A.; Feng, Yufei; Korczak, Jędrzej; Szczerbakow, Andrzej; Story, Tomasz; Peng, Zijian; These, Albert; Barabash, Anastasia; Osvet, Andres; Brabec, Christoph; et al. (Advanced Functional Materials, 2024)
Metal halide perovskite semiconductors have demonstrated remarkable progress not only in photovoltaics and X-ray detection but also in laser technologies. Particularly appealing is the simplicity with which micro-crystallites can be epitaxially grown, thereby forming micro-resonators suitable for lasing. Here, the laser threshold is optimized by selecting excitation laser parameters and by improving material quality. The latter process is conducted for formamidinium lead tribromide, emitting in the green spectral range. Depending on the growth method and parameters, the sizes of the micro-resonators can be tuned between ≈3 and 23 micrometers. Under laser excitation systematically lower thresholds are observed for micro-resonators in the 4–7 micrometer size range, than for larger ones, irrespective of growth method. Among three optimized growth methods, epitaxial growth via antisolvent vapor-assisted crystallization exhibits the smallest threshold powers, indicating the highest material quality. This conclusion is supported by hyperspectral microscopic luminescence imaging and by transient photoluminescence. The best laser structures exhibit record threshold powers for epitaxially grown perovskites, indicating that the selected antisolvent vapor epitaxial growth holds great promises also for other perovskite materials.
CRIS-Team Scopus Importer:2024-05-10
Keywords: FAPbBr; lasing; micro-resonators; perovskites; solution epitaxy

Surface versus Bulk Currents and Ionic Space-Charge Effects in CsPbBr3 Single Crystals - Almora Rodriguez, Osbel; Matt, Gebhard; These, Albert; Kanak, Andrii; Levchuk, Ievgen; Shrestha, Shreetu; Osvet, Andres; Brabec, Christoph; Garcia-Belmonte, Germa (Journal of Physical Chemistry Letters, 2022)
CsPbBr3 single crystals have potential for application in ionizing-radiation detection devices due to their optimal optoelectronic properties. Yet, their mixed ionic-electronic conductivity produces instability and hysteretic artifacts hindering the long-term device operation. Herein, we report an electrical characterization of CsPbBr3 single crystals operating up to the time scale of hours. Our fast time-of-flight measurements reveal bulk mobilities of 13-26 cm(2) V-1 s(-1) with a negative voltage bias dependency. By means of a guard ring (GR) configuration, we separate bulk and surface mobilities showing significant qualitative and quantitative transport differences. Our experiments of current transients and impedance spectroscopy indicate the formation of several regimes of space-charge-limited current (SCLC) associated with mechanisms similar to the Poole-Frenkel ionized-trap-assisted transport. We show that the ionic-SCLC seems to be an operational mode in this lead halide perovskite, despite the fact that experiments can be designed where the contribution of mobile ions to transport is negligible.
CRIS-Team WoS Importer:2022-06-10